2019 41st Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2019
DOI: 10.1109/embc.2019.8857628
|View full text |Cite
|
Sign up to set email alerts
|

Capturing concussion related changes in dynamic balance using the Quantified Y Balance Test – a case series of six elite rugby union players

Abstract: Some rights reserved. For more information, please see the item record link above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(39 reference statements)
0
5
1
Order By: Relevance
“…Evidence of other concussion studies have reported alterations in nonlinear measures of movement control and balance performance within concussed athletes. 6,23 In contrast to the present study, individuals with a history of concussion presented with reductions in approximate entropy and SEn measures. The observed differences between the current study (eg, greater movement) and previous research (eg, reduced movement) may relate to variations in postconcussion follow-up time.…”
Section: Discussioncontrasting
confidence: 98%
“…Evidence of other concussion studies have reported alterations in nonlinear measures of movement control and balance performance within concussed athletes. 6,23 In contrast to the present study, individuals with a history of concussion presented with reductions in approximate entropy and SEn measures. The observed differences between the current study (eg, greater movement) and previous research (eg, reduced movement) may relate to variations in postconcussion follow-up time.…”
Section: Discussioncontrasting
confidence: 98%
“…Importantly, these impairments were not highlighted by traditional clinical assessments, but were captured using inertial sensor technology. These findings are part of a growing body of evidence demonstrating that deficits in sensorimotor function may exist beyond clinical recovery post-concussion, 6,7,39 contributing to an increased risk of future injury. 4 As such, clinicians and rehabilitation specialists should introduce targeted balance training interventions into the return to play process to accelerate sensorimotor control recovery and mitigate the risk of future injury.…”
Section: Perspecit Vementioning
confidence: 80%
“…The primary aim of this study was to investigate if a single inertial sensor, similar to those embedded within smartphones, can capture differences in dynamic balance performance in National Collegiate Athletics Association division 1 (NCAA D1) athletes with and without a history of concussion. As sports-related concussion has previously been shown to result in the adoption of a more constrained and predictable movement control strategy, 6,16,17 in the present study, it is hypothesized that the concussive injury would result in the adoption of a more constrained and predictable movement strategy during the YBT reach excursions. Additionally, while research has demonstrated that athletes may be at risk of sustaining future musculoskeletal injury for up to 2 years following a sports-related concussion, 4 little attention has been paid to the effect of time since injury on these persistent sub-clinical deficits.…”
mentioning
confidence: 83%
See 2 more Smart Citations